AIP Conference Proceedings 2010
DOI: 10.1063/1.3377794
|View full text |Cite
|
Sign up to set email alerts
|

Protective Agent-Free Synthesis of Colloidal Cobalt Nanoparticles

Abstract: Spherical colloidal cobalt (Co) nanoparticles of about 2−7 nm were synthesized by hydrazine reduction in ethylene glycol at 80˚C. The mean diameter of the Co nanoparticles was varied to some extent by changing the pH, temperature, Co(II) chloride hexahydrate concentration, and amount of hydrazine. The Co particle size was reduced by decreasing Co(II) chloride concentration and increasing amount of hydrazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The resulting yellow solution was equilibrated at ambient temperature and vacuum-evaporated. The products were separated by TLC (silica gel, aluminum oxide sheets Si 60 F 254 , 5 × 10 cm, EMD Chemicals, Gibbstown, NJ) using hexane-ethyl acetate (80:20 v/v). , Yield, 75%. The initial compounds moved with the solvent front; the product observed under UV ( R f ≈ 0.5) was separated and dissolved in 250 μL of CD 3 OD.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting yellow solution was equilibrated at ambient temperature and vacuum-evaporated. The products were separated by TLC (silica gel, aluminum oxide sheets Si 60 F 254 , 5 × 10 cm, EMD Chemicals, Gibbstown, NJ) using hexane-ethyl acetate (80:20 v/v). , Yield, 75%. The initial compounds moved with the solvent front; the product observed under UV ( R f ≈ 0.5) was separated and dissolved in 250 μL of CD 3 OD.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a proper choice of the polyol is important, having the reducing potential suitable to carry out the reduction of the cobalt precursor. It has been shown that increasing the temperature and pH of the reaction mixture increase the rate of the overall reaction [253] . While the reduction of metal salts with borohydride is very fast, occurring at room temperature and producing relatively small NPs, the reduction using polyol is usually slow.…”
Section: Preparation Of Cobalt Nanoparticlesmentioning
confidence: 99%
“…Balela and coworkers reported a facile low‐temperature synthesis of colloidal Co NPs by reduction of CoCl 2 ⋅ 6H 2 O in EG [253] . The obtained colloidal particles were spherical and monodispersed with an average diameter of 2–7 nm.…”
Section: Preparation Of Cobalt Nanoparticlesmentioning
confidence: 99%
“…It should be noted that due to the instrumental limits of the HRTEM approach, we were able to detect the growth process of the nanoparticles with a minimum diameter of 1.5 nm for Ni and Co, instead of detecting the nucleation process . Nevertheless, these are in a good agreement with the recently reported minimal diameters of ∼1 nm Ni and ∼2 nm Co , nanocrystallites. Moreover, we have revealed that the growth of metal nanoparticles (Ni or Co) inside the organic matrix is accompanied by (i) a constant lattice parameters (within the metrical error, Figure S21A), (ii) constant lattice orientation in space (Figure S21B–E), and (iii) the constant spatial position of the nanoparticle over time (Figure S9).…”
Section: Resultsmentioning
confidence: 99%